City Networks — Expectations and reality from an ecological perspective - Strauss, Katja (Raumforschung und Raumordnung | Spatial Research and Planning, 1999)
Closer inspection of remarks which have been made on the subject of “city networks” reveals the expectations pinned to the creation and development of city networks in discussions on regional planning policy to be both great and varied. A three-year study was undertaken to establish the extent to which these expectations are indeed being met in the actual outcomes of partnerships within existing city networks. The overall results reveal a major discrepancy between the underlying spatialplanning goals and the concrete results of co-operation.